41 Burns (Pediatric Plastic and Reconstructive Surgery, 2018)
Reconstruction of pediatric burns have improved recently. Management is based on the principles of wound healing and scar maturation. Tissue can be manipulated with topical and intralesional modalities, local tissue rearrangements, grafts,  and photomedicine.
Keywords: pediatric; burn; scar; reconstruction; skin graft; laser